A qualitative study of specialist schools' processes of eliciting the views of young people with autism spectrum disorders in planning their transition to adulthood. (25th January 2018) - Fayette, Rainart; Bond, Caroline
Abstract : Government legislation and research literature highlight the importance of the participation of pupils with autistic spectrum disorders (ASD) in planning for their transition to adulthood. However, effective processes which enable their participation are under‐researched. In this study, nine teaching staff from two specialist schools in the north‐west of England were interviewed and a transition meeting was observed in one school to explore these processes. Analyses indicate that in both schools, enabling the participation of young people with ASD in the planning for their transition to adulthood involves three phases and is underpinned by a person‐centred ethos. Although the processes were perceived to be effective, the participation of pupils varied between schools. Final decisions still tend to be made by schools and the local authority due to limited external resources. The implications of these findings are discussed.